Subgingival Delivery of Statins as an Adjunct in the Non-Surgical Treatment of Periodontitis: A Systematic Review - Magdalena Maria Pietrzko; Maciej Pietrzko; Wojciech Niemczyk; Dariusz Skaba; Rafał Wiench (Biomedicines)
Background/Objectives: The gold standard in the non-surgical treatment of periodontitis is scaling and root planning (SRP). In recent years, studies have emerged suggesting additional clinical benefits from the use of statins as an adjunct to classical periodontal disease treatment. The aim of the present study was to review the relevant literature relating to the subgingival use of statins as an adjunctive treatment to the classical, non-surgical treatment of periodontitis, with a particular focus on groups with general factors that may affect the outcome of treatment. Methods: The authors conducted a systematic review following the PRISMA 2020 guidelines. The electronic literature search conducted included the MEDLINE (PubMed) database, Web of Science, Scopus, and Google Scholar from 1 January 2012 to 14 June 2024. The keywords used for the PubMed search were determined with the help of the MeSH Browser Tool and were as follows: Periodontitis [Mesh] AND Statin [Mesh] OR Simvastatin [Mesh] OR Atorvastatin [Mesh] or Rosuvastatin Calcium [Mesh]. Based on the authors’ inclusion and exclusion criteria, 20 results were included in the review, out of 937. Results: The improvement was more pronounced in patients without systematic diseases compared to those with type II diabetes and in non-smokers compared to smoking patients. Greater improvements in clinical and radiological parameters were seen in patients diagnosed with aggressive periodontitis compared to patients with chronic periodontitis. Conclusions: This literature review led the authors to the conclusion that statins applied locally might be competent agents for improving the therapeutic outcomes of SRP.